Neuroticism and Fear of COVID-19. The Interplay Between Boredom, Fantasy Engagement, and Perceived Control Over Time - Caci, Barbara; Miceli, Silvana; Scrima, Fabrizio; Cardaci, Maurizio (Frontiers in Psychology, 2020)
The Italian government adopted measures to prevent the spread of COVID-19 infection from 9 March 2020 to 4 May 2020 and imposed a phase of social distancing and self-isolation to all adult citizens. Although justified and necessary, psychologists question the impact of this process of COVID-19 isolation on the mental health of the population (e.g., Lee, Jobe & Matis, 2020). Hence, this paper investigated the relationship between neuroticism, boredom, fantasy engagement, perceived control over time, and the fear of COVID-19. Specifically, we performed a cross-sectional study aimed at testing an integrative moderated mediation model. Our model assigned the boredom to the mediation role, and both the fantasy engagement and perceived control of time to the role of moderators in the relationship between neuroticism and the fear of COVID-19. A sample of 301 subjects, mainly women (68.8%), aged between 18 and 57 years (Mage= 22.12 years; SD = 6.29), participated in a survey conducted in the first-week lockdown phase 2 in Italy from 7 to 18 May 2020. Results suggested that neuroticism is crucial in coping with the COVID-19 pandemic, in line with literature showing high neurotic people having greater emotional reactivity and scarce resources to manage stress (Larsen & Ketelaar, 1991). We also found that people with high neuroticism tend to feel bored, and the relationship between neuroticism and boredom seems enhanced if one is involved in negative fantasies. Therefore, this result could also explain the positive effect between boredom and fear of COVID-19 we found in the current study. However, our data show that perceived control over time moderates the association between boredom and fear towards COVID-19. Having a high perceived control over time allows people to reduce boredom’s effect on fear of COVID-19. In conclusion, we retain that psychological treatment programs could improve the individuals’ perceived control over time to modulate anxiety toward the fear of COVID-19 and promote psychological well-being.